The production of care in the routine of Family Health Teams - Regina Cavalcante Agonigi; Simone Mendes Carvalho; Mary Ann Menezes Freire; Lucas Fernandes Gonçalves
ABSTRACT Objective: To identify the factors interfering in the production of care in the daily work of health professionals from the Primary Health Care. Method: Qualitative research carried out with Family Health Strategy (FHS) teams, in the health units of Rocinha (Rocinha is a favela located in the South Zone of the city of Rio de Janeiro, Brazil). To analyze the data, the thematic network proposed by Attride-Stirling was used. Results: The routine of Teams in the Production of Care was the denomination of the network formed by the following themes: scales of services of the teams; structural problems of Family Health Units; standardization of protocols; challenges for the production of care; and collections of micro and macro management. Final considerations: The production of care by Family Health Teams is challenged when they take care beyond what is imposed in the organizational protocols of the FHS, reflecting the complexity of working and caring in territories with social disparities.